2011
DOI: 10.3390/v3010047
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of CMX001 as a Post Exposure Antiviral in New Zealand White Rabbits Infected with Rabbitpox Virus, a Model for Orthopoxvirus Infections of Humans

Abstract: CMX001, a lipophilic nucleotide analog formed by covalently linking 3-(hexdecyloxy)propan-1-ol to cidofovir (CDV), is being developed as a treatment for smallpox. In the absence of human cases of smallpox, new treatments must be tested for efficacy in animal models. Previously, we demonstrated the efficacy of CMX001 in protecting New Zealand White rabbits from mortality following intradermal infection with rabbitpox virus as a model for smallpox, monkeypox and for treatment of adverse reactions to smallpox vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 16 publications
3
54
0
Order By: Relevance
“…These results show that BCV is an effective agent against multiple variola virus strains in vitro. Previous studies have demonstrated in vivo antiviral activity of BCV in numerous animal models of orthopoxvirus infection, including ectromelia virus in mice and rabbitpox virus in rabbits (12,13). Therefore, the current results support further development of BCV for the treatment of smallpox.…”
supporting
confidence: 59%
“…These results show that BCV is an effective agent against multiple variola virus strains in vitro. Previous studies have demonstrated in vivo antiviral activity of BCV in numerous animal models of orthopoxvirus infection, including ectromelia virus in mice and rabbitpox virus in rabbits (12,13). Therefore, the current results support further development of BCV for the treatment of smallpox.…”
supporting
confidence: 59%
“…In rabbits, a single dose of 20 mg/kg BCV administered up to 4 days postchallenge rescued animals from lethality after intradermal infection with rabbitpox virus, with additional doses providing added therapeutic benefit (23). In mice, five daily administrations of BCV at 6.7 mg/kg, 8 mg/kg, and 10 mg/kg were sufficient to protect mice from lethality induced by infection with cowpox virus, ectromelia virus, and VACV, respectively (22,35).…”
Section: Discussionmentioning
confidence: 94%
“…Inside cells, brincidofovir is metabolized to CDV and subsequently phosphorylated to CDV-PP. Brincidofovir has potent broad-spectrum antiviral activity, including against poxviruses in vitro, and was shown to provide protection from lethality in several animal models, including mouse intranasal infections with ectromelia virus, cowpox virus, and VACV and a rabbit/rabbitpox virus intradermal challenge model (21)(22)(23). Because BCV's mechanism of action involves inhibition of viral replication, its potential effect on the elicitation of protective immunity by live smallpox vaccines is of interest.…”
mentioning
confidence: 99%
“…Body temperature has been observed to be an excellent indicator of both disease and the host response to infection (9,17,18,20). Therefore, the timing of the change in body temperature, as well as the maximum, is important in gauging the level of response to an infection.…”
Section: Intradermal Versus Scarification Infection Of Rabbits the Omentioning
confidence: 99%
“…Criteria for euthanizing the rabbits included openmouth breathing, severe difficulty in breathing, or a loss of body weight greater than 20% from the beginning initial weight. These criteria are the established euthanasia criteria for the rabbit model previously published and correspond to mortality; however, no animals were permitted to succumb to disease (9,17,18). In all animals noted in this publication, euthanasia was dictated by severe respiratory failure, defined as less than 40 breaths per minute and/or open-mouth breathing upon stimulation.…”
Section: Cells and Viruses (I) Cell Culturementioning
confidence: 99%